Analisis Pengendalian Bahan Baku Konsentrat Menggunakan Metode Economic Order Quantity (EOQ) Dan Min-Max Pada Perusahaan Pakan Ternak - Dika Aprian Fratama (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
UD Merapi Farm is a company operating in the livestock industry. In its activities, UD Merapi Farm is still experiencing problems in managing the supply of raw materials for concentrate production. UD Merapi Farm purchased around 10,176.58 kg of polar and the average remaining final inventory each month was around 828 kg. Copra meal is around 7,486.42 kg and the average remaining final inventory per month is around 282.16 kg. Palm oil meal is around 7,755.75 kg and the average remaining final inventory each month is around 356 kg. Meanwhile, ground corn is around 1,423.67 kg and the average remaining final inventory each month is around 273 kg, therefore it can be said that the amount of inventory and requirements is often not appropriate or accurate. The total inventory costs produced using the EOQ method are lower than the total inventory costs using the Company method and the Min-Max method that have been issued by the company. The total cost of raw material supplies according to UD Merapi Farm is IDR 82,359,124, according to the Min-Max method calculation the total cost is IDR 77,607,382, while according to EOQ calculations, the total cost is only IDR 56,509,208. Thus, there is potential for savings from raw material inventory costs incurred by UD Merapi Farm.